The relationship of personality, alexithymia, anxiety symptoms, and odor awareness: a mediation analysis - Binfeng Zhang; Xiuxia Li; Hongzhen Deng; Peixuan Tan; Wanyong He; Shuling Huang; Lu Wang; Hao Xu; Lei Cao; Guanghui Nie (BMC Psychiatry, 2024)
Abstract Objective Personality, emotions, and olfaction exhibit partial anatomical overlap in the limbic system structure, establishing potential mechanisms between personality, affective disorders, and olfactory-related aspects. Thus, this study aims to investigate the associations among the Big Five personality traits, alexithymia, anxiety symptoms, and odor awareness. Methods A total of 863 college participants were recruited for this study. All participants completed the Chinese Big Five Personality Inventory-15, the Odor Awareness Scale (OAS), the Toronto Alexithymia Scale-20, and the Generalized Anxiety Disorder Screener-7. Structural equation modeling was employed to examine the hypothesized mediated model. Results The findings revealed the majority of significant intercorrelations among the dimensions of the Big Five personality traits, alexithymia, anxiety symptoms, and OAS (|r| = 0.072–0.567, p < 0.05). Alexithymia and anxiety symptoms exhibited a serial mediation effect between neuroticism and OAS (95%CI[0.001, 0.014]), conscientiousness and OAS (95%CI[-0.008, -0.001]), and extraversion and OAS (95%CI[-0.006, -0.001]). Anxiety symptoms mediated the relationship between agreeableness and OAS (95%CI[-0.023, -0.001]) and between openness and OAS (95%CI [0.004, 0.024]). Conclusion The mediating roles of alexithymia and anxiety symptoms between the Big Five personality traits and odor awareness support the idea of a certain level of association among personality, emotions, and olfaction, with the underlying role of the limbic system structure. This enhances our understanding of personality, emotions, and olfaction and provides insights for future intervention measures for affective disorders and olfactory dysfunctions.